Cuba: from Columbus to Castro - Jaime Suchlicki (Brassey's (US), 1990)
The book describes how Cuba's relationship with the Soviet Union intensified, how the Kremlin applied leverage on Cuban developments, how Castro shifted toward a domestic program of economic recovery, and how Cuba increased its world presence. The book speculates on Cuba's future role in hemispheric affairs, in southern Africa, and among the dwindling communist nations of the world. The book provides a detailed and sophisticated understanding of the Cuba of yesterday, today, and tomorrow